KONTEKSTUALISASI PEMBERITAAN INJIL TERHADAP BUDAYA SLAMETAN SUKU JAWA DI DESA BADES JAWA : THE CONTEXTUALIZATION OF GOSPEL PREACHING ON THE JAVANESE SLAMETAN CULTURE IN BADES VILLAGE, EAST JAVA - Oniaman Buulolo; Linda Dewi Terserani Lase; Moralman Gulo (EIRENE (JURNAL ILMIAH TEOLOGI), 2023)
The Gospel is a good news that should be accepted by everyone. However, the Javanese in Bades Village, East Java, need to be reached with the preaching of the Bible, in view of the minimal number of believers in the local village. However, to reach this village, it is necessary to make an effort so that the Gospel conveyed can be accepted by local residents, namely through the contextualization of the slametan culture which is a Javanese culture that is already inherent in people's lives which is entrusted as anticipation for safety and unwanted disturbances that refers to a peaceful life. The purpose of this research is to find out the form of contextualization of the preaching of the Bible on slametan culture that can be done to reach people from the village of Bades Lumajang, East Java. The method used in this writing is a descriptive qualitative research method with an approach to library data, interviews, book literature and also several articles that are relevant to the research being conducted. This research conveys that in order to preach the gospel to people in Bades Village, East Java, this must be adjusted using the accommodation and adaptation contextualization model which is an act of respecting local culture, being able to express and translate the Bible through slametan culture, so that the people of East Java Those in Bades Village have true knowledge about God and accept Christ as God and eternal savior. Keywords: Contextualization, Bible, Slametan Culture, Javanese Tribe.